An active‐radio‐frequency‐identification system capable of identifying co‐locations and social‐structure: Validation with a wild free‐ranging animal. Issue 12 (17th July 2017) - Ellwood, Stephen A.; Newman, Chris; Montgomery, Robert A.; Nicosia, Vincenzo; Buesching, Christina D.; Markham, Andrew; Mascolo, Cecilia; Trigoni, Niki; Pasztor, Bence; Dyo, Vladimir; Latora, Vito; Baker, Sandra E.; et al.
Abstract: Behavioural events that are important for understanding sociobiology and movement ecology are often rare, transient and localised, but can occur at spatially distant sites e.g. territorial incursions and co‐locating individuals. Existing animal tracking technologies, capable of detecting such events, are limited by one or more of: battery life; data resolution; location accuracy; data security; ability to co‐locate individuals both spatially and temporally. Technology that at least partly resolves these limitations would be advantageous. European badgers ( Meles meles L.), present a challenging test‐bed, with extra‐group paternity (apparent from genotyping) contradicting established views on rigid group territoriality with little social‐group mixing. In a proof of concept study we assess the utility of a fully automated active‐radio‐frequency‐identification (aRFID) system combining badger‐borne aRFID‐tags with static, wirelessly‐networked, aRFID‐detector base‐stations to record badger co‐locations at setts (burrows) and near notional border latrines. We summarise the time badgers spent co‐locating within and between social‐groups, applying network analysis to provide evidence of co‐location based community structure, at both these scales. The aRFID system co‐located animals within 31.5 m (adjustable) of base‐stations. Efficient radio transmission between aRFIDs and base‐stations enables a 20 g tag to last for 2–5 years (depending on transmission interval). Data security was high (data stored off tag), with remote access capability. Badgers spent most co‐location time with members of their own social‐groups at setts; remaining co‐location time was divided evenly between intra‐ and inter‐social‐group co‐locations near latrines and inter‐social‐group co‐locations at setts. Network analysis showed that 20–100% of tracked badgers engaged in inter‐social‐group mixing per week, with evidence of trans‐border super‐groups, that is, badgers frequently transgressed notional territorial borders. aRFID occupies a distinct niche amongst established tracking technologies. We validated the utility of aRFID to identify co‐locations, social‐structure and inter‐group mixing within a wild badger population, leading us to refute the conventional view that badgers (social‐groups) are territorial and to question management strategies, for controlling bovine TB, based on this model. Ultimately aRFID proved a versatile system capable of identifying social‐structure at the landscape scale, operating for years and suitable for use with a range of species.